Institutionalizing Green Islam: Divergent Pathways of Food-Waste Governance in Indonesia’s Sharia Hotels - Rakhman Priyatmoko; Narila Mutia Nasir; Said Fahmi; Jenny Veronika Samosir (Studia Islamika, 2026)
This study aimed to investigate how Sharia hotels in Indonesia institutionalized Islamic values, including Green Islam, the principles of anti-isrāf (avoiding extravagance), anti-tabdhīr (avoiding wastefulness), and Islamic philanthropy, within food waste management practices. Drawing on a comparative case study of seven Sharia hotels in Aceh, West Nusa Tenggara, and Yogyakarta, the study found that the implementation of the values varied according to institutional capacity, leadership, and regional waste governance. The result showed that Sharia-hotel certification does not yet address food waste management. It further contributed to Islamic studies and sustainable tourism scholarship, as well as underscored the potential of Sharia hotels to serve as pioneers of halal tourism and drivers of environmental sustainability in Indonesia and Southeast Asia, by outlining micro-level practices in Sharia hotels.